Competition policy : theory and practice - Motta, Massimo (Cambridge ; New York : Cambridge University Press, 2004)
The first book offering a systematic treatment of the economics of antitrust or competition policy.
Includes bibliographical references and index.
oif 17/09/15
Loan
Keywords: Competition; Competition -- Government policy; Competition, International; Antitrust law; Industrial policy